Features of simulation of the technical parameters of the packaging line for single food products - Derenivska, Anastasiia; Kryvoplias-Volodina, Liudmyla; Tokarchuk, Serhii (My University, 2019)
The modern development of scientific and technological process is based on new directions in the creation and design of technical equipment and technical systems. In this article considers research results of packaging line work, as technical system, for single food products which includes different technical equipment. Creating a new product packaging line is involved the need for analysis, systematization of many parameters of constituent mechanisms, devices, modules, packaging equipment, transport systems and choose of optimal ones. The main parameters for the selection of equipment are technological; technical; conditions of compatibility of mechanisms, devices, modules; overall dimensions and weight, electric energy consumption indicators; economic indicators; efficiency of capital costs for its purchase, place and put into operation; payback period of the packaging machine or line. To organize a multi-stage packaging process is necessary to solve the following problems: to distribute the flow of products between the same modules to increase line productivity, to determine the required amount of modules, to determine the operating modes and required productivity of all packing line modules, to create a single orderly lined product stream from many ones in the final stages of packaging, to ensure uniformity of output product based on a uniform calculated clock cycles. Research of the products moving at the stages and levels of packaging, analysis of the intensity of products moving in transport systems and modules give the opportunity to visual observe of the products moving; to find an optimal load and number of the same type of modules; to distribute the products flow between them; to find rational kinematic parameters for work of transport systems and modules; to provide product moving incessant during changing product moving direction and distributing streams during forming a one stream from several; to ensure a uniform release of products based on the same calculated clock cycles of line packaging.
Keywords: packaging; transporting; food; пакування; транспортування; харчові продукти; кафедра мехатроніки та пакувальної техніки